2017
DOI: 10.1186/s13099-017-0179-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and immunological findings in gnotobiotic piglets infected with Escherichia coli O104:H4 outbreak strain and EHEC O157:H7

Abstract: BackgroundShiga toxin (Stx) producing Escherichia coli (E. coli) (STEC) is the most frequent cause of diarrhoea-positive haemolytic uraemic syndrome (D + HUS) in humans. In 2011, a huge outbreak with an STEC O104:H4 strain in Germany highlighted the limited possibilities for causative treatment of this syndrome. The responsible STEC strain was found to combine Stx production with adherence mechanisms normally found in enteroaggregative E. coli (EAEC). Pathotypes of E. coli evolve and can exhibit different adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…In accordance with our recent observations in EHEC-infected gnotobiotic piglets ( 25 ) and with the finding by Sauter et al in Stx2-challenged mice ( 33 ), we found low leukocyte counts in both models that were accompanied by persistent neutrophilia. There is some evidence that neutrophilia directly contributes to Stx2 toxicity as mortality and kidney damage are reduced in a murine model of HUS using polymorphonuclear-cell-(PMN)-depleted mice ( 56 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In accordance with our recent observations in EHEC-infected gnotobiotic piglets ( 25 ) and with the finding by Sauter et al in Stx2-challenged mice ( 33 ), we found low leukocyte counts in both models that were accompanied by persistent neutrophilia. There is some evidence that neutrophilia directly contributes to Stx2 toxicity as mortality and kidney damage are reduced in a murine model of HUS using polymorphonuclear-cell-(PMN)-depleted mice ( 56 ).…”
Section: Discussionsupporting
confidence: 94%
“…In our study, acute or subacute progression of HUS-like disease in mice was induced by application of different doses of Stx2, purified from the well-characterized EHEC O157:H7 patient isolate 86-24 originating from a HUS outbreak in the USA ( 35 ). Apart from being the causative agent for HUS in humans, this strain reproducibly induced a HUS-like disease in gnotobiotic piglets ( 22 , 24 , 25 ). In contrast to other studies, we injected Stx2 i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[117][118][119] A more comprehensive review of the use of pigs colonized with human GM is provided by Wang and Donovan. 113 Similarly, piglets delivered via cesarean section can be monocolonized 120,121 or colonized with a highly restricted defined microbiota similar to Altered Schaedler Flora used in mice 122,123 to tightly control GM composition.…”
Section: Pigs (Sus Scrofa Domesticus)mentioning
confidence: 99%
“…Although full maturation with CD8 + T cells and IgA + B cells occurs within 7 weeks, lymphoid structures within GALT develop an adult architecture by 10-15 days, and are populated by CD4 + lymphocytes and IgM producing B between 2-4 weeks. 17 Due to lack of maternal antibody and premature gut immune system, GB piglets are very susceptible to human enteric pathogens such as rotavirus, 18 Shiga toxin producing Escherichia coli, [19][20][21] Shigella spp., 22 Clostridium difficile, 23 and Cryptosporidium spp. [24][25][26] The clinical symptoms and the mucosal lesions induced, location and distribution by these agents in GB piglets, are similar or identical to those observed in humans.…”
Section: The Gnotobiotic Piglet: a Model Of Cryptosporidiosismentioning
confidence: 99%